Remission of hypertension after surgical cure of Cushing's syndrome. (9th December 2019) - Jha, Smita; Sinaii, Ninet; McGlotten, Raven N.; Nieman, Lynnette K.
Abstract: Context: Hypertension associated with Cushing's syndrome (CS) increases cardiovascular risk. The time‐course of improvement after cure is unclear. Objective: To describe the time‐course and predictors of blood pressure (BP) normalization during one year after surgical cure of CS. Design: Retrospective chart review of 75 hypertensive adults cured of CS (72 with ACTH‐dependent CS; 3 with adrenal adenoma). Hypertension was defined as current use of antihypertensives, a systolic BP >130 mm Hg, or diastolic BP >80 mm Hg. Main Outcome Measure(s): Remission of hypertension: BP ≤130/80 mm Hg and no antihypertensive medications. Improvement in hypertension: BP >130/80 mm Hg and decreased number or dose of medications, or blood pressure ≤130/80 with continued use of medications at constant dose. Results: At postoperative discharge, 17 (23%, P  < .001), 51 (68%, P  < .001) and 7 (9%) patients had remission, improvement in hypertension or no change. Twenty‐nine had no follow‐up. Others achieved remission at 3 (n = 5), 6 (n = 6), or 12‐months (n = 5). At the last evaluation, 33/75 (44%) had remission, 36/75 (48%) had improved hypertension and 6 were unchanged. Patients with improvement discontinued a median of one medication ( P  < .001). At 12‐months, 27/42 (64%) patients had normal BP ( P  < .002). Longer estimated duration of CS ( P  = .0106), younger age ( P  = .0022), and lower baseline body mass index ( P  = .0413) predicted hypertension remission. Conclusions: About 80% of CS patients experienced BP normalization or improvement within 10 days of cure, but about half failed to normalize BP by one year. BP should be monitored after cure, and antihypertensive medications adjusted to avoid unwanted cardiovascular effects.